2018
DOI: 10.1097/aud.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Same or Different: The Overlap Between Children With Auditory Processing Disorders and Children With Other Developmental Disorders: A Systematic Review

Abstract: Children diagnosed with APD perform equally to children diagnosed with SLI, dyslexia, ADHD, and LD on tests of intelligence, memory or attention, and language tests. Only small differences between groups were found for sensory and perceptual functioning tasks (auditory and visual). In addition, children diagnosed with dyslexia performed poorer in reading tasks compared with children diagnosed with APD. The result is possibly confounded by poor quality of the research studies and the low quality of the used out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 87 publications
1
41
0
1
Order By: Relevance
“…We agree with Moncrieff (2017) that it is valuable to investigate whether the performance of children with APD is different from the performance of children with another developmental disorder, such as SLI, dyslexia, LD, attention-deficit/hyperactivity disorder, or autism spectrum disorder. That is why we carried out a second review (de Wit et al, 2018) in parallel with the first review (de Wit et al, 2016), in which we described the differences and similarities in performance to different outcome measurements between children diagnosed with APD, SLI, dyslexia, attention-deficit/hyperactivity disorder, and LD. The results of this second review (de Wit et al, 2018) confirm our initial observation that the behavior of children with a diagnosis of APD broadly corresponds to the behavior of children diagnosed with another developmental disorder.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with Moncrieff (2017) that it is valuable to investigate whether the performance of children with APD is different from the performance of children with another developmental disorder, such as SLI, dyslexia, LD, attention-deficit/hyperactivity disorder, or autism spectrum disorder. That is why we carried out a second review (de Wit et al, 2018) in parallel with the first review (de Wit et al, 2016), in which we described the differences and similarities in performance to different outcome measurements between children diagnosed with APD, SLI, dyslexia, attention-deficit/hyperactivity disorder, and LD. The results of this second review (de Wit et al, 2018) confirm our initial observation that the behavior of children with a diagnosis of APD broadly corresponds to the behavior of children diagnosed with another developmental disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is inconclusive evidence from which it can be concluded that APD can be clearly differentiated from other neurodevelopmental disorders with overlapping symptoms. Most, if not all, cases of childhood APD are characterized by more generally acknowledged learning disabilities (4). Thus, we conclude the opposite: APD cannot be differentially diagnosed at the moment because there are no valid methods to accurately do so.…”
Section: Apd As a Distinct Diagnosismentioning
confidence: 99%
“…Two extensive systematic reviews (from 1954 up to May 2015) showed that: (1) The characteristics of children suspected of APD and diagnosed with APD are neither specific nor limited to the auditory modality. Significant differences were found on auditory and visual functioning, cognition, language, reading, physiological measures and brain structure and activity between children referred with listening difficulties and typically developing children (24); (2) Children diagnosed with APD and children diagnosed with developmental language disorder, dyslexia, attention deficit disorder, and learning difficulty shared overlapping characteristics in terms of intelligence, memory, attention and language (4). Based on these results, we argue that there is inconclusive evidence for the existence of a specific auditory deficit in children currently diagnosed with APD.…”
Section: Auditory Processing and Cognitive Skillsmentioning
confidence: 99%
“…Many studies have indicated the comorbidity of APD with other growth disorders. Observations suggested that some types of childhood neuropsychological disorders such as attention-deficit/ hyperactivity disorder (ADHD), language disorders, learning disorders and autism spectrum disorders may lead to behaviors similar to those of APD or APD as a disorder associated with other neurophysiological disorders [6,7]. Learning disability (LD) means an impairment in one or more of the psychophysiological processes that manifests itself in the understanding and use of spoken or written language [7].…”
Section: Introductionmentioning
confidence: 99%